Heat Shock and Its Consequences on Early Life Performance of Stripped Catfis (Pangasianodon hypophthalmus) - Prama Hartami; Odang Carman; Muhammad Zairin; Alimuddin Alimuddin (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
Researchers have widely applied heat shock on zygote stadia of domesticated aquatic animals especially for the purpose of ploidy manipulation in fish to accelerate growth, intermediate products for the production of infertile seeds, providing prospective brood stock as well as the monosex population. This is certainly an interesting study to see how far the impact of heat shock on the early development stages. This experiment used a 42 0C heat shock for 2.5 minutes on the zygote at different initial time i.e. 28.5; 29; 29.5; 30 and 30.5 minutes after fertilization. All treated larvae and control were reared in a 25 liters plastic container at density of 5 larvae per liter. The results showed that high percentage of fertilization rate were 92.61 % to 96.32 % and hatching rate was 85.33 % without any abnormalities were achieved in the control. While in all treatments had a very low hatching rate of 4.12 % to 8.93 % with relatively high abnormalities of 12.36 % to 27.60 % and a significant differences (P<0.05) compared to controls, but survival rate, specific growth rate and feed conversion ratio after 30 days rearing period showed no significant difference (P>0,05). In terms of seed production, the heat shock treatment will limit 78 % to 82 % of larvae production.